2015
DOI: 10.1039/c5cp03400k
|View full text |Cite
|
Sign up to set email alerts
|

Plasma induced tungsten doping of TiO2 particles for enhancement of photocatalysis under visible light

Abstract: Here we report a novel method for modifying commercially available TiO2 nanoparticles by a microwave-induced plasma technique. After the plasma treatment TiO2 nanoparticles showed enhanced visible absorption due to the doped W atoms, and the photocatalytic methylene blue degradation above 440 nm was successfully improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
(38 reference statements)
1
11
0
Order By: Relevance
“…Introducing reactive gas and sputter systems, which allow manipulation of energies and chemical state of the sputtered atoms/clusters, for doping multiple metal NPs and for synthesizing desired compounds and structures can be also considered for sputtering onto liquids towards advanced nanomaterials. Regarding production of metal, metal alloy and hybrid nanoparticles with wide variety of morphologies, higher ordered structure, doping and functionalization, we have demonstrated that our solution synthesis approaches based on chemical reduction, plasma in liquid process and stabilizing agents are very versatile [120][121][122][123][124][125][126] though in many cases toxic chemicals and by-products are present as they are also expected in other reports. Hence, we encourage and welcome other researchers join investigating this new vacuum sputtering onto liquid method, take all of its great advantages as the green technique for pure nanoparticles and unexpected structures, as well as devote new ideas for achieving more versatile control of the sputtered NPs.…”
Section: Summary and Prospectssupporting
confidence: 61%
“…Introducing reactive gas and sputter systems, which allow manipulation of energies and chemical state of the sputtered atoms/clusters, for doping multiple metal NPs and for synthesizing desired compounds and structures can be also considered for sputtering onto liquids towards advanced nanomaterials. Regarding production of metal, metal alloy and hybrid nanoparticles with wide variety of morphologies, higher ordered structure, doping and functionalization, we have demonstrated that our solution synthesis approaches based on chemical reduction, plasma in liquid process and stabilizing agents are very versatile [120][121][122][123][124][125][126] though in many cases toxic chemicals and by-products are present as they are also expected in other reports. Hence, we encourage and welcome other researchers join investigating this new vacuum sputtering onto liquid method, take all of its great advantages as the green technique for pure nanoparticles and unexpected structures, as well as devote new ideas for achieving more versatile control of the sputtered NPs.…”
Section: Summary and Prospectssupporting
confidence: 61%
“…[9,[14][15][16] Although the recent advancements of using TiO 2 -NP provide the high-quality products in our daily life, the modification of TiO 2 -NP is critical to achieve the high efficiency in the utilization of the solar energy. [2] Due to the wide band gap energy (≈ 3.2 eV, corresponding to a wavelength of 380 nm to 390 nm), [2,4,5,7] the bare TiO 2 -NP (i.e., without modification) has been reported to be mainly active in the UV and the near-UV range of the electromagnetic spectrum. Besides, the high recombination rate of photogenerated hole-electron pairs of TiO 2 -NP was also reported to be a critical issue to the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] The advantages of TiO 2 -NP include low cost, high chemical and thermal stability, ready availability, ease of handling, and non-toxicity. [4,5,9,10] The functional response of TiO 2 -NP is fundamentally governed by the generation of charge carrier by photons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various H 2 O 2 detection techniques that have been developed, which include spectrometry, fluorescence, and chromatography, the electrochemical methods offer special combinational advantages like low detection limit, high plasmas have been used to grow polymer films on different substrates [28]. Tungsten-doped TiOx nanoparticles (NPs) were obtained through the modification of commercially available TiO 2 NPs using plasma processing [29]. Tungsten trioxide NPs were synthesized by microwave plasma treatment [30].…”
Section: Introductionmentioning
confidence: 99%